2017
DOI: 10.1002/adma.201605043
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Defect Domains in Single‐Crystalline Hexagonal WS2

Abstract: Single-crystalline monolayer hexagonal WS is segmented into alternating triangular domains: sulfur-vacancy (SV)-rich and tungsten-vacancy (WV)-rich domains. The WV-rich domain with deep-trap states reveals an electron-dedoping effect, and the electron mobility and photoluminescence are lower than those of the SV-rich domain with shallow-donor states by one order of magnitude. The vacancy-induced strain and doping effects are investigated via Raman and scanning photoelectron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
146
4
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 26 publications
6
146
4
2
Order By: Relevance
“…This correlation of PL Stokes shift with absorption peak energy, but not with PL emission peak energy, strongly supports increased electron doping in the dark regions and, particularly, the narrower regions indicated in the insets of Figure 3, although we do not exclude the possible effects of minor compressive strain in the dark regions. 14,64 Away from these narrow regions connecting the centre to the apexes (i.e. in the yellow regions in the inset of Figure 3d), the slope of the correlation between Stokes shift and Aexciton absorption peak energy is reduced to β ∼ 0.52 and the strength of the correlation is also slightly reduced, with the Pearson's correlation coefficient down to 0.8.…”
Section: Resultsmentioning
confidence: 97%
“…This correlation of PL Stokes shift with absorption peak energy, but not with PL emission peak energy, strongly supports increased electron doping in the dark regions and, particularly, the narrower regions indicated in the insets of Figure 3, although we do not exclude the possible effects of minor compressive strain in the dark regions. 14,64 Away from these narrow regions connecting the centre to the apexes (i.e. in the yellow regions in the inset of Figure 3d), the slope of the correlation between Stokes shift and Aexciton absorption peak energy is reduced to β ∼ 0.52 and the strength of the correlation is also slightly reduced, with the Pearson's correlation coefficient down to 0.8.…”
Section: Resultsmentioning
confidence: 97%
“…A recently reported result suggests that the presence of either an S or W vacancy is more likely to lower the Raman frequency in a hexagonal WS 2 single crystal. 36 In this manner, the relatively softened E 2g 1 vibrations in both hexagonal mono-and bilayer MoS 2 likely result from an effect of vacancy induced defect states. We also studied the Raman spectral changes of triangular MoS 2 crystals with regards to various stacking orientations and thicknesses ranging from 1L to 6L.…”
Section: Synthesis Of Multi-stacked Mos 2 Crystalsmentioning
confidence: 99%
“…As illustrated by a recent study regarding a hexagonal WS 2 monolayer, defect states can be a key factor in reducing the PL emission in a localized fashion. 36 Moreover, the tailored PL intensity is also related to the band structure change via an extra-strain effect induced by merged defects. 37 The broadened and redshifted PL spectrum of the hexagonal monolayer compared to that of the triangular monolayer indicates the possible involvement of defect-assisted quenching in the PL emission.…”
Section: Synthesis Of Multi-stacked Mos 2 Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In optical properties, Carozo et al 66 reported lowtemperature defect-bound excitons in the edge regions of monolayer WS 2 due to the presence of a high concentration of monosulfur vacancies. Heterogeneous distributions of sulfur vacancies and tungsten vacancies have also been identified by Jeong et al, 67 thus forming triangular domains in hexagonal shaped WS 2 islands, which result in a segmented alternating photoluminescence (PL) intensity pattern. In bandgap engineering, a recent study on a quaternary alloy system, Mo x W 1-x Se 2(1-y) S 2y , has been reported by Susarla et al, 68 allowing a wider continuous tuning range (1.60~2.03 eV) than the ternary systems of Mo x W 1-x X 2 (X = S, Se) and MSe 2(1-x) S 2x (M = Mo, W).…”
Section: Structure-property Correlation Of Point Defects In 2d Matementioning
confidence: 75%